Peran Media Pembelajaran dalam Meningkatkan Pemahaman Materi Bangun Ruang pada Siswa Sekolah Dasar - Nania Zumairoh Azzahra Putri; Febriani Ardia Wardani; Widia Putri Lestari; Anugrah Puty Damayanti; Adhe Aulia Rodhiah (Universitas PGRI Madiun, 2026)
The topic of three-dimensional shapes is a mathematics unit taught in elementary schools that often poses challenges for many students. This difficulty arises because the concept of three-dimensional shapes is abstract, whereas the cognitive abilities of elementary school students are typically still at the concrete operational stage. Consequently, students often struggle to recognize three-dimensional forms, understand the relationships between the components of these shapes, and apply this knowledge when solving mathematical problems. To address this issue, there is a need for learning media that can present concepts in a more tangible way, thereby making the learning process easier to comprehend. This study aims to examine and summarize research findings regarding the effectiveness of learning media in enhancing elementary school students' understanding of three-dimensional shape concepts, utilizing a literature review approach. The study employed a literature review method, drawing upon scientific articles from accredited national journals and reputable international journals relevant to the research focus. Reference materials were gathered from various academic databases and analyzed using content analysis to identify patterns, similarities, and differences among published studies. The results indicate that the use of various types of learning media such as concrete objects, manipulatives, instructional videos, interactive presentations, animations, and Augmented Reality (AR) technology positively impacts the learning of three-dimensional shapes. These media not only help students better grasp concepts and develop visual-spatial skills but also boost learning enthusiasm, encourage active participation, and improve mathematics learning outcomes. The synthesized findings suggest that learning media are crucial for bridging abstract geometric concepts with tangible learning experiences, resulting in a more effective, meaningful, and learner-centered educational process. Therefore, selecting learning media that align with the nature of the subject matter and the students' cognitive developmental stage should be a top priority for improving the quality of instruction on three-dimensional shapes in elementary schools.